Strategi Pemerintah Dalam Menertibkan PKL Di Pasar Oesao Dan Pasar Lili Kabupaten Kupang - Melaniati Suharni; Vinsensius Tamelab; Ferdinandus Lobo (Universitas Sains dan Teknologi Komputer, 2023)
A street vendor is any individual or organization that seeks or trades on a sidewalk, boulevard, yard/yard, or other place not intended for it. The regulation and arrangement of street vendors is an important issue for local governments in many regions. This is because urban population growth and rapid urbanization have resulted in an increase in demand for accessibility and diversity of goods and services. MPAs emerged in response to this need, but uncontrolled growth can lead to significant overcrowding and space limitations. The research method used in this study is sociological or empirical legal research, which includes research on legal identification (unwritten) and research on legal effectiveness. There are many obstacles faced by the Kupang regency government in controlling and managing street vendors at the Oesao market and Lili market, such as the lack of communication between the parties, both the government as an institution that issues policies, the community and traders who are used as objects; the ineffectiveness of the efforts issued by the Kupang district government in providing socialization and also the inadequate selling places that have been built by the Kupang district government. The strategy made by the Kupang regency government in controlling street vendors at the Oesao market and Lili market, namely providing strategic places to sell by building markets far from public routes; Updating facilities and infrastructure and improving cleaning and security services.